Pharmacist intervention to improve adherence to medication among heart failure patients at North East Ethiopia hospital - Abate Wondesen Tsige; Tsegaye Ababiya Kotiso; Kassahun Dires Ayenew; Siraye Genzeb Ayele (Wiley, 2024)
Abstract Heart failure (HF) is a major and growing medical problem and its management is still challenging due to the coexistence of complications, co‐morbidity, and medication non‐adherence. HF patients who are adherent to their medication have fewer HF exacerbations, improved survival, and lower healthcare expenditure. Adherence to HF medication plays a pivotal role in attaining maximal therapeutic outcomes. The aim was to assess the medication adherence of heart failure patients at Debre Berhan Comprehensive Specialized Hospital (DBCSH). A pre‐post interventional study was undertaken from July 1, 2022, to December 31, 2022, at the medical referral clinic of DBCSH. The educational interventions were provided for 6 months. Medication adherence was determined using the Morisky Green Levin Medication Adherence Scale (MGLS). The data was entered into Epidata version 4.2.0 and analyzed using SPSS version 25.0 statistical software. Descriptive statistics and binary logistic regression analysis were performed. The strength of the association between predictor variables and outcome variables was determined using a 95% confidence interval and adjusted odd ratio. In the pre‐intervention phase, 54.6% of patients had medium medication adherence, while in the post‐intervention phase, 36.4% of patients had high medication adherence and 61.9% of patients had medium medication adherence. Following the intervention, medication cost (120, 50%), inadequate availability of drugs (75, 31%), and forgetfulness (30, 13%) were the main reasons for medication non‐adherence. The presence of co‐morbidity and the number of co‐morbidity (p < .05) were significantly associated with the occurrence of decreased medication adherence in the pre‐intervention phase. Interventions by pharmacists to educate HF patients about the nature of their disease and providing brochures to increase awareness of their medications have been shown to improve medication adherence.